Analisis Morfologi Kelas Kata Terbuka Pada Editorial Media Cetak - Ismayasari, Rina; Pastika, I Wayan; Putu Putra, A. A. (Humanis, 2016)
The study "Analysis of Morphology Class Password Open the Print Media Editorial" aims to determine the type of noun, verb type, and the type of adjectives in editorial print media. Moreover, to know the how the process morphology when viewed in terms of form, function and meaning of the word class open to editorial print media. The theory used is the structural linguistic theory to the theory of word classes and morphology theory developed Gorys Keraf and Harimurti. At this stage of data collection used methods refer assisted by freely refer techniques and techniques involved capably record. Phase analysis of data using qualitative descriptive methods and at the stage of presentation of the results of data analysis used informal methods. Research analysis of morphological classes of words open the print media editorial discusses the type of noun that is divided into nouns in terms of semantic, syntactic, and shapes. Types of verbs divided into verbs and verbs derived free basis. Type adjectives are divided into basic adjectives and adjectival derivative. In addition, the open word classes morphological analysis on the print media's editorial discusses the morphological processes open word class which is classified into three, namely affixation, reduplication and compounding.